Study on the evolution mechanism of mechanical properties of recycled concrete excited by different alkali content at high temperature - Su, Qing; Tao, Zhixiong (Frontiers in Mechanical Engineering, 2025)
IntroductionAt present, the gradual reduction of sand and gravel stock is very unfavorable to the preparation of recycled concrete.MethodsTherefore, this study focused on alkali excited recycled concrete with different dosage of copper slag, and set different high temperature methods to test its mechanical properties.ResultsThe results showed that: 1) The residual compressive strength of the control group was not as good as that of the experimental group under other high temperature effects except for the experimental group under 400°C; 2) After high temperature action at 200°C, the ratios of A30, B30 and C30 relative to normal temperature are 1.07, 1.11 and 1.12 respectively, which are slightly higher than those after high temperature action at 400°C, indicating that the use of a certain amount of copper slag to replace fine aggregate quartz sand is helpful to improve the performance of alkali-stimulated recycled concrete at high temperature; 3) The flexural strength of A30 and A60 was 1.410 times and 1.371 times that of the control group after high temperature reaction at 800°C, indicating that the addition of copper slag had a positive impact on the flexural strength of alkali stimulated recycled concrete. 4) After treatment at 200°C, the bending strength ratios of control groups, A30, A60 and A100 were 0.676, 0.748, 0.728 and 0.687, respectively, while after treatment at 600°C, the corresponding ratios were 0.349, 0.440, 0.437 and 0.382, respectively, indicating that the addition of copper slag in high temperature environment, the bending strength ratio of control groups was 0.676, 0.748, 0.728 and 0.687, respectively.DiscussionIt can improve the flexural strength of alkali excited recycled concrete. Through this research, we can make due contributions to the sustainable development of the construction industry. The novelty lies in the qualitative and quantitative analysis of the mechanical properties of this recycled concrete doped with steel slag under high temperature conditions, and the results obtained are better than the high temperature resistance of conventional recycled concrete, which has a new breakthrough in performance.